1994
DOI: 10.2527/1994.7281964x
|View full text |Cite
|
Sign up to set email alerts
|

A genetic study of estrus symptoms at puberty and their relationship to growth and leanness in gilts

Abstract: Puberty traits of 740 Yorkshire gilts from a selection experiment were analyzed. Heritabilities were estimated to be .32 for pubertal age, .23 for length of proestrus, .16 for length of standing estrus, .29 for ability to show standing reflex, and .24 for intensity of vulvar symptoms. Genetic correlations between length of proestrus, intensity of vulvar symptoms, and ability to show standing reflex were positive. There seemed to be a negative genetic correlation between percentage of lean and intensity of vulv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
37
0
2

Year Published

1995
1995
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(46 citation statements)
references
References 0 publications
7
37
0
2
Order By: Relevance
“…However, gilts with greater growth rate and backfat have shorter weaning to estrus intervals (Tummaruk et al, 2001) and age at puberty is positively genetically correlated with weaning to estrus interval and signs of estrus (Sterning et al, 1998). In reviewing growth and puberty reports, Rauw et al (1998) noted that gilts with a greater lean percentage had a delayed onset of puberty, and negative genetic correlations have been reported between growth rate and estrus signs at puberty (Rydhmer et al, 1994). Leptin has long been recognized as a putative signal that links metabolic status with the neuroendocrine control of reproduction and puberty in pigs, and attainment of puberty may be related to a metabolic state at a critical period of development rather than a level of body composition (Rozeboom et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…However, gilts with greater growth rate and backfat have shorter weaning to estrus intervals (Tummaruk et al, 2001) and age at puberty is positively genetically correlated with weaning to estrus interval and signs of estrus (Sterning et al, 1998). In reviewing growth and puberty reports, Rauw et al (1998) noted that gilts with a greater lean percentage had a delayed onset of puberty, and negative genetic correlations have been reported between growth rate and estrus signs at puberty (Rydhmer et al, 1994). Leptin has long been recognized as a putative signal that links metabolic status with the neuroendocrine control of reproduction and puberty in pigs, and attainment of puberty may be related to a metabolic state at a critical period of development rather than a level of body composition (Rozeboom et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…Booth et al (1994) called attention to the significant effect of feeding intensity on metabolic and reproductive status. According to Rydhmer et al (1994), gilts with a higher genetic capacity for growth had a lower genetic capacity for oestrous traits than those with a lower growth rate. The possible effect of an adequate feeding regime and nutritional manipulation on metabolic and reproductive function deserves special attention (Booth et al, 1994;Rozeboom et al, 1995;Klindt et al, 1999;Ji et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Selection aimed at improving the meatiness and reducing the fatness of gilts may lead to a belated attainment of sexual maturity, resulting in a delay of the first farrowing (Mucha et al, 2010). The negative correlations between excessive muscularity and the reproduction performance of gilts and sows have been demonstrated in numerous studies (Rydhmer et al, 1994;Tummaruk et al, 2007;Stančić et al, 2011).The aim of this work was to assess the impact of muscularity degree on growth and development of the reproductive system in gilts prior to attaining sexual maturity. …”
mentioning
confidence: 99%
“…Several significant QTL for average daily gain and average backfat thickness have been mapped at a position close to the QTL region found in this study [6,18]. It has been shown that age at puberty shows high genetic correlations with body weight [30], growth rate and fatness in pigs [10,25]. The overlapping QTL region for age at puberty, growth and fatness traits indicates that there might be gene(s) with pleiotropic effects on these traits in the region.…”
mentioning
confidence: 99%
“…Because ages at puberty and weaning to oestrus interval are positively correlated [27] and the primary reason for culling sows is failure to return to oestrus after weaning; selection for younger pigs at puberty has a favourable effect on sow reproductivity [13]. Although the average heritability estimated for puberty age in gilts is 0.32 [25], ages at puberty and oestrus cycles are very laborious to measure. Thus, marker-assisted selection (MAS) may provide a practical and efficient method to improve age at puberty in gilts.…”
Section: Introductionmentioning
confidence: 99%